CHILD, YOUTH AND PUBLIC POLICY IN PORTO ALEGRE - Barcellos Guimarães, Evandro (2010)
This article will be held a reflection on childhood, youth from some public policiesimplemented by the municipality of Porto Alegre in the period 2001 to 2007. The sources usedfor this work will rely on the research in books and articles that address these issues. Search willbe the implementation of these policies in Porto Alegre, from the Project for Urban Security inPorto Alegre and Project "Opening Space": School Open. The Children and Youth are concepts,invented earlier time, if we take into account the time of development of society. It was in thenineteenth century and XX that occurred the emergence of childhood as a social issue. Tornadois the subject of public policies of the state from the Code of Children of 1979 that says less iswhat is private subexistenciais conditions, health and compulsory education, representation andassistance, because of lack, action or omission or manifest impossibility of parents or guardians.And only from the half of the twentieth century is that they perceive the implementation ofpublic policies aimed at children and youth. School Open Program is a project of education,culture, sport and work for the youth and the Project for Public Security of Porto Alegre enablesus to think portoalegrense the ability of society to organize itself. As result of the experience ofthe Participatory Budget, seen as a pioneer in the country. This project is aimed at combating thetrafficking of arms and drugs for youth, crimes against equity, violence against women andchildren, the reintegration of Community egressos the prison system, the construction of a studio or multimeios experimental station of popular cultural invention , in addition to providing anenvironment that contribute to the pool circuit Peace through workshops on education: sports,environmental, and conservation of cultural heritage.